Ski jumping flight skill analysis based on high-speed video image - Murakami, M.; Iwase, M; Seo, K.; Ohgi, Y.; Koyanagi, R. (Procedia Engineering, 2010)
Mages of the initial 40m part of a flight of 120-m ski jumping were recorded by a fixed high-speed video camera in Hakuba Ski Jumping Stadium. The time variations of the forward leaning angle and the ski angle of attack were measured from the video image and the aerodynamic forces were calculated from kinematic data. Some correlations were investigated between the reduced jumping distance Dr, which is an initial speed corrected flight distance, and some key angles and the initial transition time, as well as those between Dr and the aerodynamic force coefficients. Jumping performance is compared between advanced jumpers and beginner jumpers.